2021
DOI: 10.1177/10711007211004151
|View full text |Cite
|
Sign up to set email alerts
|

Do Coronal or Sagittal Plane Measurements Have the Highest Accuracy to Arthroscopically Diagnose Syndesmotic Instability?

Abstract: Background: To compare the accuracy of arthroscopic sagittal versus coronal plane distal tibiofibular motion toward diagnosing syndesmotic instability. Methods: Arthroscopic assessment of the syndesmosis was performed on 21 above-knee cadaveric specimens, first with all ligaments intact and subsequently with sequential transection of the anterior inferior tibiofibular ligament, the interosseous ligament, the posterior inferior tibiofibular ligament, and the deltoid ligament. A lateral hook test, an anterior-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The intraoperative open hook test was performed to confirm the instability of the syndesmosis. 7 If the posterior malleolus was fractured and the involved articular surface was more than 25% of the tibial plafond, it was fixed with cannulated screws after reduction.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The intraoperative open hook test was performed to confirm the instability of the syndesmosis. 7 If the posterior malleolus was fractured and the involved articular surface was more than 25% of the tibial plafond, it was fixed with cannulated screws after reduction.…”
Section: Surgical Techniquementioning
confidence: 99%
“…92 (Figure 6) Arthroscopy helps measure dynamic diastasis and distinguish instability in multiple planes. 20,93 Bhimani et al 94 performed a cadaveric study and reported that arthroscopic measurement of sagittal plane fibular translation is more accurate than coronal plane diastasis for evaluating syndesmotic instability.
Figure 6.Arthroscopic view is demonstrated widening of syndesmosis (long white arrow) and rupture of AITFL (*) (4(a)), drive-through is positive by inserting 3-mm shaver (S) into syndesmotic joint (4(b)), the syndesmotic joint is reduced after syndesmotic fixation (4(c), small white arrow), and AITFL is intact after open repair (4(d), *) (Ti = Tibia, Ta = Talus, F = fibula, * = AITFL, and S = Shaver).(With copyright permission from Chamnanni Rungprai; Salubris Publishers).
…”
Section: Investigationsmentioning
confidence: 99%
“…128 Arthroscopy is another method used to identify instability as well as verify reduction. 20,93,94 Operative treatment of syndesmotic Injuries with assisted arthroscopic reduction has been reported. 129…”
Section: Operative Treatmentmentioning
confidence: 99%
“…The specimens were mounted to a wooden board using 5-mm Schanz pins inserted anteroposteriorly into the proximal, middle, and distal aspects of the tibia. 3,20…”
Section: Specimen Preparationmentioning
confidence: 99%